2005
DOI: 10.1104/pp.104.054213
|View full text |Cite
|
Sign up to set email alerts
|

Green Sperm. Identification of Male Gamete Promoters in Arabidopsis

Abstract: Previously, in an effort to better understand the male contribution to fertilization, we completed a maize (Zea mays) sperm expressed sequence tag project. Here, we used this resource to identify promoters that would direct gene expression in sperm cells. We used reverse transcription-polymerase chain reaction to identify probable sperm-specific transcripts in maize and then identified their best sequence matches in the Arabidopsis (Arabidopsis thaliana) genome. We tested five different Arabidopsis promoters f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 34 publications
6
148
0
Order By: Relevance
“…However, transcriptome studies of isolated sperm cells showed that sperm cells contain thousands of transcripts, consistent with transcriptional activity (13,30). This idea is supported by the identification of several sperm cell-specific genes, such as GEX1 and DUO1 (31,32). Nevertheless, the extent of active transcription in plant sperm cells remains to be investigated, because some transcripts identified in the sperm cell transcriptome might have been transported from the vegetative cell during pollen development.…”
Section: A Combination Of Sequences In the 5′ Utr And Coding Region Arementioning
confidence: 80%
“…However, transcriptome studies of isolated sperm cells showed that sperm cells contain thousands of transcripts, consistent with transcriptional activity (13,30). This idea is supported by the identification of several sperm cell-specific genes, such as GEX1 and DUO1 (31,32). Nevertheless, the extent of active transcription in plant sperm cells remains to be investigated, because some transcripts identified in the sperm cell transcriptome might have been transported from the vegetative cell during pollen development.…”
Section: A Combination Of Sequences In the 5′ Utr And Coding Region Arementioning
confidence: 80%
“…GhSWEET1a_At/Dt, GhSWEET2a_At/Dt, GhSWEET5_At/ Dt,GhSWEET7a_At/Dt, GhSWEET9_At/Dt, GhSWEET15-c_At/Dt highly expressed in floral organs, indicating different members of the GhSWEETs family in cotton expressed in different parts of the flower and in different developmental stages. AtSWEET1/4/5/7/8, AtSWEET13/14/ 15 have a relatively high level of expression in floral organs of Arabidopsis (Feng et al 2015;Engel et al 2005;47 Wellmer et al 2006). OsSWEET1a/2a/3a/4/5/15 in rice also showed relatively high expression levels at different developmental stages of flowers and panicles (Feng et al 2015).…”
Section: Expression and Putative Functions Of Sweetsmentioning
confidence: 99%
“…The highly conserved GCS1/ HAP2 gene encoding a secreted membrane protein is essential for fertilization in a myriad of other eukaryotes as well (Mori et al, 2006;von Besser et al, 2006;Liu et al, 2008). Additional male gamete-selective genes have been identified and characterized in lily and Arabidopsis (Engel et al, 2005;Okada et al, 2005aOkada et al, , 2005bBrownfield et al, 2009aBrownfield et al, , 2009b.…”
Section: Mgsa Sites Determine Selective Activation Of Pzipt1 Promotermentioning
confidence: 99%
“…Another lily gene, GCS1, and its Arabidopsis homolog HAP2 are expressed in sperm cells and are essential for fertilization (Mori et al, 2006;von Besser et al, 2006). Sperm cell-expressed genes GAMETE EXPRESSED 1 (GEX1) and GEX2 were identified in maize sperm cell-specific transcripts, and homologous Arabidopsis genes were designated AtGEX1 and AtGEX2 (Engel et al, 2005). AtGEX1 is expressed in sperm cells of mature pollen in Arabidopsis.…”
mentioning
confidence: 99%